Strategi Guru PAI dalam Meningkatkan Disiplin Siswa di UPT SD Negeri 060941 - Rokan, Nurliza Dewi; Widyawati, Winda; Cintia, Cintia (Yayasan Rahmat Islamiyah, 2024)
This research aims to determine the role and strategies of PAI teachers in improving learning discipline at the UPT SD Negeri 060941 School. This research uses qualitative observation with a data collection methodology through interviews, observation and documentation. Research results obtained: Values and Ethics approach in learning Islamic Religious Education, Implementation of Interactive and Creative Learning Methods in Islamic Religious Education, Teacher's role as a role model in forming student discipline.